Artificial network inference analysis reveals the impact of biostimulant on bacterial communities in fumigated soil for potato production against common scab - Tekeu, Honoré; Jeanne, Thomas; D’Astous-Pagé, Joël; Hogue, Richard (Frontiers in Soil Science, 2023)
As part of a study on control methods of common scab disease impact on potato yield and quality, high-throughput sequencing was used to measure the effects of soil fumigant chloropicrin alone or in combination with a Bacillus spp.-based biostimulant on soil bacterial diversity in terms of richness and composition, as well as on soil bacterial network interactions. The results showed that common scab caused significant net yield losses of more than 46.25% in potatoes of control plots (T1), while the use of the fumigant alone (T3) and the use of the fumigant with the biostimulant (T4) reduced net yield losses to less than 2.5%. These treatments also promoted gross yield increases of 23.5 cwt. acre -1 (7.06%) and 28 cwt. acre -1 (8.41%) respectively. The study found that using the soil fumigant chloropicrin significantly and persistently altered the composition of the soil bacterial community over the growing season. The modifications of the soil bacterial community induced by the inoculation of the Bacillus spp-based biostimulant are distinct by the end of the growing season depending on whether the soil has been fumigated (T4)or not (T2). Interestingly, artificial network inference analysis showed that the T2 treatment had the highest number of edges and linkages, contrary to the T3 treatment that had the lowest number of edges and linkages. The fumigation alone treatment leads to a reduction in interactions, while the application of the biostimulant, in both non-fumigated and fumigated soil, results in increased interactions and a higher number of connections within a phylum or between different taxa. Furthermore, the treatment combining the fumigant and the biostimulant exhibits a moderate increase in various network properties, providing evidence for the positive effect of biostimulant inoculation on bacterial communities in fumigated soils. Our results provide a more detailed understanding of the bacterial community structure and diversity in the soil of the different treatments. Moreover, deciphering network interactions in soil bacterial communities is fundamentally important for research in soil microbial ecology of potato cropping systems.